Mathematics

Question

5 (- 3 x - 2) - (x - 3) = - 4 (4 x + 5) + 13

2 Answer

  • PEMDAS
    parentheses, exponent, multiplication/division, addition/subtraction
    first, start with what is inside the parentheses that is solvable.
    5(6) - (x-3) = -4(4x+5) + 13
    multiply what you can
    30 - (x-3) = -16x - 20 + 13
    simplify
    30 - (x-3) = -16x - 7
    subtract 30 on both sides
    - (x-3) = -16x - 37
    let’s separate -(x-3).
    -x - 3 = -16x - 37
    add 16x to both sides
    15x - 3 = -37
    add 3 to both sides
    15x = -34
    x = -34/15 or -2.2667
  • Answer:

    Step-by-step explanation:

    5 (- 3 x - 2) - (x - 3) = - 4 (4 x + 5) + 13

    Opening brackets

    -15x - 10 - x + 3 = -16x - 20 + 13

    -16x -7 = -16x - 7

    Collecting like terms

    -16x + 16x = -7 + 7

    0x = 0

    No possible solution for x

NEWS TODAY